Students' Effective Communication Experiences in Friends: A Phenomenological Study - Ferdiansyah, Muhammad; Kalfahny, Rara Collin; Putri, Amelia; Putry, Willy Ade; Luvitasari, Vivit; Sintia, Bella (Faculty of Education Universitas Negeri Malang, 2024)
Abstract: Along with advances in science and technology, more and more women are starting to play roles in the public sector, one of which is by working. In this context, married women who work are said to have a dual role because apart from being wives and housewives, mothers also act as career women. The aim of this research is to analyze students' experiences of communicating in friendships, with a focus on effective communication. Using qualitative methods with a phenomenological approach, data was collected through observation, in-depth interviews and documentation. The research results show that there are four main keys to communicating effectively in friendship, namely regulating emotions and adjusting communication style, not forcing your will and being sensitive to the atmosphere, preparing feedback strategies and overcoming communication difficulties, and using expressions and body movements.